Analysis of the Influence of the Implementation of Risk Management and Murabahah Financing on the Financial Performance of the Benteng Mikro Indonesia Sharia Cooperative - Faisal, Riza (Budapest International Research and Critics University, 2024)
This study deals with Analysis of the Influence of the Implementation of Risk Management and Murabahah Financing on the Financial Performance of the Benteng Mikro Indonesia Sharia Cooperative. The study used a descriptive method to describe factually, an accurate description of the facts, and to find out the relationship between phenomena and the variables studied. The results of this study are 1) The financial performance of the cooperative is to describe the cooperative's activities in utilizing existing resources to achieve goals in order to achieve financial aspects. 2) Murabahah financing can occur in sharia cooperatives by fulfilling the characteristics of the pillars of murabahah financing that have been mutually agreed upon between the two. 3) Risk management is carried out so that risks can be minimized, so that plans and targets that have been set can be realized so that they produce results.